2019
DOI: 10.1530/rep-18-0527
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the connection between GABA and kisspeptin in the control of reproduction

Abstract: Neuroendocrine control of reproduction involves the interplay of various factors that become active at some point along development. GnRH is the main neurohormone controlling reproduction and among the most important inputs modulating GnRH synthesis/secretion are GABA and kisspeptins. These interactions of GABA and kisspeptin in the control of GnRH secretion can take place by the presence of the receptors of both factors on the GnRH neuron or alternatively by the actions of GABA on kisspeptin neurons and/or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 78 publications
0
12
1
Order By: Relevance
“…Previous studies in camelids have reported this delay in animals treated with SP or NGF obtained from SP [53, 54] or when GnRH analogues are administered by intravaginal route [37]. The explanation for this delay in the LH peak is unclear, although Adams et al [55] suggested it could be the consequence of an unknown intermediate step in the ovulation pathway required for GnRH/LH release because the regulation of GnRH secretion in neurons depends on numerous inputs [56]. One of these inputs can be provided by interneurons such as kisspeptins and noradrenergic neurons after NGF interaction, as postulated by Carrasco et al [57].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in camelids have reported this delay in animals treated with SP or NGF obtained from SP [53, 54] or when GnRH analogues are administered by intravaginal route [37]. The explanation for this delay in the LH peak is unclear, although Adams et al [55] suggested it could be the consequence of an unknown intermediate step in the ovulation pathway required for GnRH/LH release because the regulation of GnRH secretion in neurons depends on numerous inputs [56]. One of these inputs can be provided by interneurons such as kisspeptins and noradrenergic neurons after NGF interaction, as postulated by Carrasco et al [57].…”
Section: Discussionmentioning
confidence: 99%
“…As the interaction between Kp and GABA is known from the literature [85,86], it also seemed possible that Kp-8 might directly affect GABA release in NAc. GABAergic neurons in the NAc have been shown to inhibit dopaminergic projections from the VTA [87].…”
Section: Discussionmentioning
confidence: 99%
“…Others believe that it will hyperpolarize GnRH neurons and inhibit GnRH secretion. In general, it mainly promotes the secretion of GnRH (52)(53)(54). Differences in the results may be related to the physiological stage of the body and the delay of GABA receptor signal transition.…”
Section: Related Research Work On Epilepsy and Pcosmentioning
confidence: 99%